Optimal Alternative Fuel Selection for Dual-Fuel Ships Under FuelEU Maritime Regulations: Environmental and Economic Assessment - Cong Wang; Zhongxiu Peng; Jianming Yang; Niyu Zhang; Ke Li; Xuesong Li (Journal of Marine Science and Engineering)
To address greenhouse gas (GHG) emissions from the maritime sector, the European Union (EU) has introduced the FuelEU Maritime regulation to incentivize ships to adopt diversified compliance pathways and energy solutions. This study aims to determine the optimal alternative fuel configurations for dual-fuel ships of different types under environmental, economic, and regulatory constraints. An integrated environmental and cost assessment model from a well-to-wake (WtW) perspective to systematically evaluate the environmental benefits and economic feasibility of fossil-based, bio-based, and renewable electricity-based alternative fuels applied in dual-fuel ships. By incorporating the PROMETHEE II method within a multi-criteria decision analysis (MCDA) framework, together with the CRITIC objective weighting method, the study enables a robust ranking of alternative fuel configurations across three key dimensions: environmental performance, cost feasibility, and regulatory compliance. The results indicate that, regardless of ship type, the very low sulfur fuel oil (VLSFO) + marine gas oil (MGO) and VLSFO + methanol (MEOH) combinations fail to meet the GHG intensity targets for 2025–2050. Only the VLSFO + electrolytic liquid hydrogen (E-LH2) and VLSFO + electrolytic ammonia (E-NH3) configurations are compliant. Although e-fuels incur the highest annual costs, the EU compliance penalty associated with fossil fuels increases exponentially. In contrast, e-fuels retain long-term cost advantages, ultimately driving a sector-wide transition toward e-fuel-dominated energy structures by 2050. Their superior environmental performance and regulatory compatibility emerge as the core drivers of the maritime energy transition.